2 - La semi-industrialisation contemporaine - JACQUEMOT , Pierre (Africa Development, 1981)
The idea of a world economic system based on the Centre-Periphery analysis cannot provide a satisfactory overall explanation of some develo ping countries real situation. New terms have appeared recently, such as «advanced developing countries» or «new industrial countries». In fact these expressions refer to economies which are yet various and heteroge neous, but which tend to be covered by a common and new category: semi-industrialization (S. I.). The paper brings out the main characteristics of 12 S. I. countries by identifying three types: «inward-looking economies» (Brazil, Argentine, Mexico), «outward-looking economies» (South Korea, Taiwan, Singapore, Hong Kong) and «mineral economies» (Nigeria, Algeria, lrak, Iran, Vene zuela). It analyses their industrial components and their accumulation pro cess, linked with their historical mode of integration in the world economy. It also raises the problem of the agrarian reform and the necessity of a seve re social discipline to maintain the low cost of the labour force. At last, the paper deals with the economic and political conditions for a completion of the industrialization in these countries. It mainly depends on their capacity to anticipate and participate to the actual changes in the industrial structure of the world economy. Pierre JACQUEMOT, Service Education Permanente, Université de Paris